Explaining the Reasons for the Extension of Students\' Study Duration and Providing Strategies to Improve the Current Situation from the Perspective of Post- Graduated Students at Tabriz University of Medical Sciences (Qualitative Study) - Raana gholamzadeh nikjoo; Fazrnaz Jamshidi Aghdam; Maryam Behjat (Journal of Medical Education and Development)
Introduction: Study duration refers to the specific period a student must complete their education. This study aims to elucidate the factors contributing to the prolonged study duration among students of the Faculty of Management and Medical Informatics at Tabriz University of Medical Sciences and to provide effectual strategies for reducing this duration. Methods: This qualitative study was conducted using a content analysis approach. The research population included all eligible graduate students (those with extended study duration) from the Faculty of Management and Medical Information in 2021 and 2022. A total of 48 students were selected using a census method. Data collection was conducted using three different tools: interviews, document reviews, and analysis of students' extension requests. Content analysis was employed to analyze the data. Results: The interview findings indicated two categories of influential factors: personal issues and university-related factors. Personal issues included employment, family problems, the overlap of studies with the COVID-19 pandemic, the distance between the university and residence, internet limitations, time gaps between undergraduate and graduate studies, and prolonged data collection. University-related factors included a lack of cooperation from professors, delays in proposal approval, strict research regulations concerning articles, and professors' rigorous demands during the thesis defense process. Conclusion: Reducing the stages of thesis approval at the university level, initiating the thesis process during the initial semesters of study, and enhancing scientific capabilities regarding thesis writing during the study period are among the strategies to improve the current situation of students' study duration.